HCV-induced increase in alpha-fetoprotein without hepatocarcinoma - Gastaldi , Francielly Marques; Gastaldi , Franciny Marques (Seven Editora, 2023)
Hepatitis C Virus (HCV) infection is chronic and is still an important cause of liver cirrhosis. In patients with chronic hepatic dysfunction, the risk of developing hepatocarcinoma is 1 to 5% per year, and may be higher in patients with other risk factors, such as alcoholism and HIV co-infection. DOI:https://doi.org/10.56238/sevened2023.006-055